2012
DOI: 10.1007/s00280-012-1852-8
|View full text |Cite
|
Sign up to set email alerts
|

TH-302, a hypoxia-activated prodrug with broad in vivo preclinical combination therapy efficacy: optimization of dosing regimens and schedules

Abstract: Purpose Subregional hypoxia is a common feature of tumors and is recognized as a limiting factor for the success of radiotherapy and chemotherapy. TH-302, a hypoxia-activated prodrug selectively targeting hypoxic regions of solid tumors, delivers a cytotoxic warhead to the tumor, while maintaining relatively low systemic toxicity. The antitumor activity, different dosing sequences, and dosing regimens of TH-302 in combination with commonly used conventional chemotherapeutics were investigated in human tumor xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 40 publications
4
98
0
Order By: Relevance
“…15,23 TH-302 is a pro-drug that is activated specifically in hypoxic cells, and has demonstrated promising results both in preclinical studies and in early clinical trials. [11][12][13]25,26 However, since TH-302 is non-fluorescent, its direct visualization in tumor tissue is not possible. Therefore, we extended our techniques of assessing biomarker distribution following drug treatment to evaluate the effects of TH-302 in hypoxic and vascular regions of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 TH-302 is a pro-drug that is activated specifically in hypoxic cells, and has demonstrated promising results both in preclinical studies and in early clinical trials. [11][12][13]25,26 However, since TH-302 is non-fluorescent, its direct visualization in tumor tissue is not possible. Therefore, we extended our techniques of assessing biomarker distribution following drug treatment to evaluate the effects of TH-302 in hypoxic and vascular regions of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that T given 2 -4 hrs before administration of conventional chemotherapeutics is an optimal schedule. 21 nP prior to G is employed in both clinica 27 and preclinical settings, 37 and it has been shown that nP is able to increase intratumoral concentration of G. 37 In this study, the animals were first dosed with TH-302 ip, followed by nP iv 2 hrs later, and then after 1 more hr, G was given ip. MTD was determined by dose escalations in a small number of CD-1 immunocompetent mice or non-tumor bearing nu/nu mice.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…TH-302 exhibits hypoxia-selective in vitro cytotoxicity cross a wide variety of human cancer cell lines 19 and in vivo anti-tumor efficacy in a panel of human tumor xenograft models. 20,21 Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive tumors in humans, with a 5-year survival rate of less than 5%. 22 Gemcitabine, a cytotoxic pyrimidine analog chemotherapeutic, has been the standard first-line treatment for patients with unresectable locally advanced or metastatic pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the efficacy of TH-302 is improved when administered before rather than after treatment with one of the above chemotherapeutic agents. Accordingly, when TH-302 is used in a combination with other conventional antineoplastic agents, the efficacy of TH-302 is affected by the order in which it is administered (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%